Climate change through the essentials–nature's offering and humankind's sine qua non - Anderl, Thomas (Frontiers in Climate, 2023)
Climate change is decomposed into the driving terms allowing long-term projection of the natural and economic impacts. As a result, in the case of carbon emissions reduction by 2 % per year from the present, the atmospheric CO2 concentration is expected to return to preindustrial values in about 1,000 years, temperature and sea level rise to approximately peak at 1 °C and 5 m above the present levels by then, and the entailed economic burden to grow to 1.4 % of the current global gross domestic product. 90 % of the required emissions reduction are anticipated achievable through cost neutrality. To take advantage of the potentially bearable impact, humankind is obliged to fulfil certain prerequisites near-time: (i) CO2 emissions reduction must be at least 2 %/year at global level; (ii) economic growth may not continue to jeopardize emissions reduction efforts, thus far contributing with an emissions rise of 1.7 %/year; (iii) due to the economic interlinkage, global coherence of regulatory measures must be established, proposedly commencing with a sizable group of countries, the rules comprising economic penalization of non-participants. The presented insight is associated with the potential to alter the social decision mode.